2012 IEEE International Symposium on Information Theory Proceedings 2012
DOI: 10.1109/isit.2012.6284061
|View full text |Cite
|
Sign up to set email alerts
|

A rate-compatible sphere-packing analysis of feedback coding with limited retransmissions

Abstract: Abstract-Recent work by Polyanskiy et al. and Chen et al.has excited new interest in using feedback to approach capacity with low latency. Polyanskiy showed that feedback identifying the first symbol at which decoding is successful allows capacity to be approached with surprisingly low latency. This paper uses Chen's rate-compatible sphere-packing (RCSP) analysis to study what happens when symbols must be transmitted in packets, as with a traditional hybrid ARQ system, and limited to relatively few (six or few… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…This is analogous to the protocol of our VLFT implementation in [3]. We note that the concept of m maximum transmissions before repetition also appears in, for example, [10], [11].…”
Section: B Two-phase Scheme With Incremental Redundancymentioning
confidence: 83%
See 2 more Smart Citations
“…This is analogous to the protocol of our VLFT implementation in [3]. We note that the concept of m maximum transmissions before repetition also appears in, for example, [10], [11].…”
Section: B Two-phase Scheme With Incremental Redundancymentioning
confidence: 83%
“…In [3], we presented a VLFT scheme with limited decoding times (corresponding to "packets"), using variable-length codes with finite maximum length formed by the puncturing of tail-biting convolutional codes. We also provided a ratecompatible sphere-packing (RCSP) analysis of the scheme and showed that the RCSP predictions closely matched the performance of simulated tail-biting convolutional codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latency improvement is made possible by capitalizing on favorable noise realizations and attempting to decode early, instead of needlessly sending additional symbols [5]. In case of an unfavorable noise realization, additional information is required which effectively lowers the communication rate to match the operational capacity of the channel.…”
Section: Vlft With Non-binary Ldpc Codesmentioning
confidence: 99%
“…Chen et al [2] and Williamson et al [5] analyzed a VLFT scheme based on rate-compatible sphere-packing with an ML decoder (RCSP-ML). RCSP is an approximation of the performance of repeated incremental redundancy with noiseless transmitter confirmation (IR-NTC).…”
Section: Introductionmentioning
confidence: 99%